Metal-free and Atom-efficient Protocol for Diarylation of Selenocyanate by Diaryliodonium Salts; Organic and Biomolecular Chemistry; Vol. 21 - iss. 33 - Radzhabov A. D. Amirbek Dzhurabekovich; Soldatova N. S. Nataliya Sergeevna; Ivanov D. M. Daniil Mikhaylovich; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Kukushkin V. Yu. Vadim Yurjevich; Postnikov P. S. Pavel Sergeevich (2023, 2023)
The rational search for the efficient protocols for atom-efficient arylation utilizing iodonium salts is the genuine need for the sustainability and green chemistry. We developed a novel approach toward metal-free diarylation of selenocyanate using trimethoxyphenyl-substituted iodonium salts with the formation of appropriate diarylselenides. The suggested procedure allows the preparation of a series of diarylselenides without isolation and purification of intermediate products in two-step one-pot sequence.